EDUKASI PERAWATAN ORGAN REPRODUKSI EKSTERNAL SAAT MENSTRUASI BAGI REMAJA PUTRI MELALUI VIDEO ANIMASI TIPE MOTION GRAPHIC - Krisciaputri, Yuliana Cornillon Intan; Wenas, Michael Bezaleel (Institut Bisnis dan Teknologi Indonesia, 2021)
This study discusses the design of a socialization video entitled Menstrual Health and Hygiene with motion graphic techniques. This is based on the importance of a woman to maintain personal hygiene, especially during menstruation and the lack of socialization media that discusses the maintenance of cleanliness and health of women's external reproductive organs, especially during menstruation. Therefore, a media outreach was designed in the form of video socialization with motion graphic techniques to help socialize how to maintain the cleanliness and health of women's external reproductive organs, especially during menstruation effectively and attractively. The method used is a mixed method for data collection and quantitative testing of product results. In this design, the process of making socialization media, from the concept design to the final result, is in the form of video socialization with motion graphic techniques. The results achieved from this research were in the form of a socialization video entitled Menstrual Health and Hygiene, able to convey information about hygiene and health of female external reproductive organs, especially during menstruation and can be used as a media for Menstrual Health and Hygiene socialization.